Analysis of the Influence of Principal Leadership Effectiveness and Work Motivation on Basic Education Teacher Competencies - Safitri, Wirda; Kasmini, Lili; Rahmatullah; Sari, Siti Mayang (Indonesian Journal of Instructional Media and Model, 2024)
The competency of teachers is a critical factor in the quality of education, and leadership as well as work motivation play vital roles in enhancing this competency. This research aims to analyze the effectiveness of school principal leadership and work motivation and their influence on the competency of basic education teachers in Pidie Regency. Using a quantitative approach with a correlational research type, the study found that the multiple linear regression equation is Y = -5.743 + 0.636X1 + 0.484X2. The leadership of primary education school principals in Pidie Regency has been effective, significantly influencing the competency of basic education teachers (Y) in Pidie Regency, with a calculated t value of 5.207 and a significance level of 0.000. The work motivation (X2) of basic education teachers in Pidie Regency is high and significantly influences their competency, with a calculated t value of 3.786 and a significance level of 0.000. Simultaneously, the variables of principal leadership effectiveness (X1) and work motivation (X2) significantly affect basic education teacher competency (Y) in Pidie Regency, with a calculated F value of 256.737 and a significance level of 0.000. The correlation coefficient (r) of 0.928 indicates a very strong and unidirectional relationship between the independent and dependent variables. The coefficient of determination (R2) of 0.861 shows that the independent variables collectively contribute 86.1% to the dependent variable, while the remaining 13.9% is influenced by other factors outside this research. This research contributes to the field of education by providing evidence of the significant impact of school principal leadership and teacher work motivation on teacher competency, highlighting the importance of effective leadership and motivation in enhancing educational outcomes.